The correlation between anemia, body mass index, parity, family history of preeclampsia with the onset of preeclampsia literature review analysis - Dewiarianti, Dewi; Triawanti, Triawanti; Panghiyangani, Roselina (Science Midwifery, 2024)
Introduction: preeclampsia is a common problem that is feared by pregnant women. Preeclampsia is one of the highest causes of maternal mortality in Indonesia. In the last 2 decades, there has been no significant decrease in the incidence of preeclampsia in Indonesia. Of all these cases, several risk factors were found, such as anemia (26%), obesity (10%), and chronic hypertension (8%), parity and family history of preeclampsia. Objective: a literature review study to determine the relationship between anemia, BMI, parity and family history of preeclampsia with the incidence of preeclampsia. Method: Literature review study for collecting scientific data, anemia, body mass index, family history of eclampsia and parity with the onset of preeclampsia. Data collection was carried out through a search of the Google Scholar Database, Crossref, Researchgate with keywords, anemia *OR* body mass index *OR* family history of eclampsia *OR* parity *OR* incidence of preeclampsia. Inclusion criteria in data collection include articles published in journals in 2021-2024, national and international journals, population and sample are pregnant women with preeclampsia. The flow of scientific article selection is depicted in the form of a PRISMA Diagram. Results: Based on the results of the database search, 30 out of 1937 articles were obtained from 3 Google Scholar databases, Crossref, researchgate, as many as 4 international articles and as many as 26 national articles, with the number of each factor, namely parity as many as 16 articles, body mass index (BMI) as many as 12 articles, anemia as many as 6 articles and family history of preeclampsia as many as 2 articles. Conclusion: Anemia, Body Mass Index, Parity and Family History of Preeclampsia are significant factors in the occurrence of preeclampsia in pregnant women.